The Profit/Gain from Islamic Law of Contract Perspective and The Issue Of Ownership Risk (Daman al‐Milkiyyah) - Tawfik Azrak; Hani Hazaa (Journal of Islamic Finance, 2021)
In Islamic finance it is crucial to discuss the concept and the meaning of al-bay’ (Sale) and subsequently the concept of “Iwad”, when anyone want to understand issues concerning shariah legitimacy in Islamic banking and finance. The sale (Albay’) or the equivalent value “Iwad”, from shariah view, should consist of three main components, namely: market risk (ghurm), the work and effort (kasab), while the third component is liability (Daman). Albay; which is trade and commerce, constitutes the Quranic alternative to riba, as the contract of sale in Islamic law requires the seller to own the subject matter before executing the sale. The prophet Muhamad (pbuh) said: “do not sell what you do not own”. Therefore, there is a strong link between ownership and market risk. This research paper is analyzing the concept of profit from Islamic law perspective and discuss the issue of ownership risk in Islamic financial contracts. Using in depth analysis of literature review and qualitative methods of content analysis, this research implicitly explains the effect of Ghurm, Kasab, and Daman on Islamic finance transactions that are based on Albay'. Further, it highlights the principle mutual trade and cooperation in Albay' transactions.